Evaluation of Ultrasonography as a Diagnostic Tool in Maxillofacial Space Infections - Praveen Kumar Pandey; Meenaxi Umarani; Sharadindu Kotrashetti; Shridhar Baliga (eJournal of Oral Maxillofacial Research, 2011)
Objectives: The purpose of the study was to establish the role of ultrasonography in determining the involvement of specific fascial spaces in maxillofacial region and the stage of infection, in indicating the appropriate time for surgical intervention and to compare clinical and ultrasonographic findings.Material and Methods: Twenty five patients with fascial space infection in maxillofacial region were subjected to ultrasonographic examination following a detailed clinical and radiological examination. Ultrasonography guided needle aspiration was performed. Based on the findings, patients diagnosed with abscess were subjected to incision and drainage and those with cellulitis were subjected to medical line of treatment.Results: More than one fascial space was involved in all patients. On clinical examination 64 spaces were involved, of them 34 spaces had abscess formation and 30 spaces were in the stage of cellulitis. On ultrasonography examination, 28 spaces were reported to have abscess formation and 36 spaces were diagnosed to be in the stage of cellulitis. On comparative analysis of both clinical and ultrasonographic findings, ultrasonography was found to be sensitive in 65% of the cases and having specificity of 80%. It was registered statistically significant (P < 0.001) agreement between these two methods of assessment (kappa index = 0.814).Conclusions: Ultrasonography is a quick, widely available, relatively inexpensive, and painless procedure and can be repeated as often as necessary without risk to the patient. Thus ultrasonography is a valuable diagnostic aid to the oral and maxillofacial surgeon for early and accurate diagnosis of fascial space infection, their appropriate treatment and to limit their further spread.